1996
DOI: 10.1006/bijl.1996.0069
|View full text |Cite
|
Sign up to set email alerts
|

Palatablility and escaping ability in Neotropical butterflies: tests with wild kingbirds (Tyrannus melancholicus, Tyrannidae)

Abstract: The palatability and the ability of neotropical butterflies to escape after being detected, attacked and captured by wild kingbirds (Tyrannus melancholicus Vieillot), was investigated by the release of 668 individuals of 98 butterfly species close to the birds, during their usual feeding activities. Most of the butterflies were attacked and eaten. Only the troidine swallowtails (Parides and Battus; Papilionidae) were consistently rejected on taste and elicited aversive behaviours in birds. Most other aposemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 29 publications
2
70
1
4
Order By: Relevance
“…In a general sense, our work supports the view that escape and unpalatability are alternative ways of avoiding attack (Pinheiro 1996). Thus, when unprofitable (unpalatable) prey were readily recognized, there was no selection on these individuals to evolve the rapid movement that necessarily evolved in profitable prey.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In a general sense, our work supports the view that escape and unpalatability are alternative ways of avoiding attack (Pinheiro 1996). Thus, when unprofitable (unpalatable) prey were readily recognized, there was no selection on these individuals to evolve the rapid movement that necessarily evolved in profitable prey.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is less well appreciated that such species also tend to exhibit slow and predictable movement (Pasteels et al 1983;Whitman et al 1985;Chai and Srygley 1990;Srygley and Chai 1990;Marden and Chai 1991;Pinheiro 1996;Hatle and Faragher 1998;Hatle et al 2002). The slow movement reported in conspicuous unprofitable species is qualitatively different from the near motionlessness exhibited by many cryptic but otherwise profitable species (those lacking significant noxious qualities once attacked).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knowledge of the defensive roles of AAs lags behind the chemical investigations; unpalatablity is more often assumed than documented. Among the species in Table 1, only for P. aristolochiae (Uesugi 1996), Troides aeacus (C. & R. Felder) (Rothschild et al 1970), Battus polydamas (L.) (Chai 1986;Pinheiro 1996), and B. philenor (L.) does some experimental evidence for unpalatability complement the chemical data.…”
Section: Introductionmentioning
confidence: 96%
“…Field observations and cage experiments have shown that adults of conspicuous ithomiines and danaines were taste-rejected by the rufous-tailed jacamars Galbula ruficauda (Galbulidae), the kingbirds Tyrannus melacholicus (Tyrannidae) and the golden lion-tamarin Leontopithecus rosalia (Callitrichidae). In contrast, cryptic butterflies, supposed to be palatable, were eaten (Brown 1985 and references therein;Chai 1986;Pinheiro 1996). The red-winged blackbird Agelaius phoeniceus (Icteridae) rejected adults of the leaf beetle O. cacaliae, which contain PAs in a secretion produced in the elytra glands, as well as in the entire body (Rowell-Rahier et al 1995).…”
Section: Hägele and Rowell-rahier (2000)mentioning
confidence: 99%